Vermicomposting of Sludge from the Camp SIC Cité-Verte Wastewater Treatment Plant (Yaounde-Cameroon) - Laure, Ngahane Emilienne; Mbappe, Tambe Roosevelt; Rodine, Tchiofo Lontsi; Joel, Sagne Moumbe (European Scientific Journal, ESJ, 2024)
In Yaounde, as in most sub-Sahara African cities, wastewater management is a major concern. Through its national sanitation strategy, Cameroonian government takes many initiatives to improve the urban sanitation situation by constructing social housing, where wastewater treatment plants are integrated. However, their purification performance is often low and the by-products represent great risk factors. This paper focuses on preserving the health of the population, reducing environmental pollution, and improving soil fertility by vermicomposting sludge from the Yaounde Camp SIC Cité-Verte wastewater treatment plant. The methodological approach consisted of the characterisation of sludge, followed by the vermicomposting test. At the end of the 35-day process, the produced vermicompost was characterized, and its agronomic efficiency was tested on waterleaf (Talinum triangulare) cultivation. The Yaounde Camp SIC Cité-Verte wastewater treatment plant consistently produces an average of 239 Kg of sludge per day. The sludge is primarily composed of high carbonaceous material (53%) and contains essential nutrients for plant growth (NPK: 13%), along with pathogenic microorganisms and heavy metals in low concentrations. The characterisation of the vermicomposts obtained after 35 days showed a conservation of nutrients (NPK) concentration and a decrease in carbonaceous matter and heavy metals. Moreover, there was a complete absence of fecal pathogens in the vermicompost of the two setups. The agronomic efficiency of the vermicomposts on waterleaf was shown by a high germination rate (100 % for vermicomposts), a high number of leaves (28 ± 15), a deep green coloration of plants, a great plant length (17.3 ± 4.6 cm), and a large stem diameter (2.1 ± 0.4 cm). The NPK content (˃7%) indicates that the vermicompost produced can be used as an agricultural organic fertilizer.